Necrotising herpetic retinopathy in patients with advance HIV disease. Issue 6 (December 1997) - Miller, R F; Brink, N S; Cartledge, J; Sharvell, Y; Frith, P
Abstract : OBJECTIVES: To describe the presenting features, clinical and laboratory diagnosis, response to treatment, and outcome of necrotising herpetic retinopathy (NHR) in HIV infected patients. METHODS: Retrospective case records/laboratory data review of five HIV infected patients presenting to the specialist HIV/AIDS unit at UCL Hospitals, London from April 1994 to August 1996 with a clinical diagnosis of NHR. RESULTS: All patients had advanced HIV disease with a median CD4 count of 20.10(6)/1. Three patients had cutaneous varicella zoster virus (VZV) infection within the preceding 8 weeks. All had uniocular loss of visual acuity; one also had headache and another ocular pain. All had typical retinal appearances. VZV DNA was detected in cerebrospinal fluid of four patients (and in vitreous fluid of one of the four) and in vitreous fluid of one other. One patient refused therapy and rapidly became blind. Four patients received intravenous foscarnet with intravenous aciclovir for 6 weeks: three subsequently received oral famciclovir and one oral valaciclovir; two patients also had intravitreal injections of foscarnet. In none of the four did treatment bring about improvement in visual acuity, but in all four visual loss from retinitis was halted. CONCLUSIONS: NHR occurs in HIV infected patients with advanced HIV disease and is strongly associated with evidence of VZV infection. With aggressive use of antiviral drugs the outcome is not uniformly poor.